New Age elements in the Clamp’s manga X - Castelli-Olvera, Sarahi Isuki (Jangwa Pana, 2017)
In this article, we start from the consideration that manga X, created by the collective CLAMP between 1994 and2003, and published in Mexico by Editorial Vid between 2002 and 2005, is a story whose overarching principle corresponds to the various elements of the New Age. We base this on the following assumptions: first in this manga, the sephirotic tree, the B.O.T.A. tarot and the aspects of Enochian magic, typical of western esoterism, are present iconographically. Second, Kamui, the subject of the story, represents God, so that his actions determine the entire narrative; besides, it has a twin star (Fuma), which fulfills the function of being its complementary opposite. Finally, the apocalypse is detonated by the well-being of the Earth, which arises as an organism with its own life and is intended to survive the destruction of humanity. We carry out this analysis taking up the notion of an overarching principle, as well as the importance of the source, present in the historical method. In addition to the above, we use the paradigm of indicial inferences proposed by Carlo Ginzburg, the elements of structural analysis of Helena Beristain’s story and the notion of postmodernity introduced by Fredrick Jameson. The primary sources would be the 18 volumes of X published in Mexico.